2015
DOI: 10.1177/0278364915578646
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ego-motion estimation from optical flow for online control of a quadrotor UAV

Abstract: Abstract-For the control of Unmanned Aerial Vehicles (UAVs) in GPS-denied environments, cameras have been widely exploited as main sensory modality for addressing the UAV state estimation problem. However, the use of visual information for ego-motion estimation presents several theoretical and practical difficulties, such as data association, occlusions, and lack of direct metric information when exploiting monocular cameras. In this paper, we address these issues by considering a quadrotor UAV equipped with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 31 publications
1
70
0
Order By: Relevance
“…When the robot hovers at ∼1.2 m, the altitude estimation error is ∼10 cm. This is comparable to the results from in [22], where a robust feature-based ego-motion estimation algorithm was shown to provide the RMS error of 9.23 cm for a flight at 1 m altitude. Our results indicate the effectiveness of the proposed implementation of the direct optic flow method and the EKF scheme that are relatively simple in comparison.…”
Section: Estimation Errors At Higher Flight Altitudesupporting
confidence: 84%
See 4 more Smart Citations
“…When the robot hovers at ∼1.2 m, the altitude estimation error is ∼10 cm. This is comparable to the results from in [22], where a robust feature-based ego-motion estimation algorithm was shown to provide the RMS error of 9.23 cm for a flight at 1 m altitude. Our results indicate the effectiveness of the proposed implementation of the direct optic flow method and the EKF scheme that are relatively simple in comparison.…”
Section: Estimation Errors At Higher Flight Altitudesupporting
confidence: 84%
“…In evidence of this, in [21], it was reported that the RMS errors in velocity estimates in flight were higher than those from a handheld experiment, citing the vibrations and motion blur as the cause of inaccuracies. Similarly, in [22], the results showed that the RMS errors of the estimated velocity To further inspect this claim, performed additional handheld experiments to imitate vertical flights in section 5. In this situation, the robot was manually moved vertically with the amplitude of ∼10 cm at the altitude of ∼40 cm, similar to the previous vertical flights.…”
Section: Effects Of Vibration On Altitude Estimationmentioning
confidence: 88%
See 3 more Smart Citations